Potensi Ekstrak Daun Ficus deltoidea Jack sebagai Anti Kanker Payudara - Rizky Clarinta Putri; Kusmardi Kusmardi; Rani Wardani Hakim (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2024)
Female breast cancer is the most common diagnosed cancer worldwide in 2020, with an estimated 2.3 million new cases or 11.7% from total 18,1 million cases, followed by lung, colorectal, prostate, and stomach cancers. In 2040, the breast cancer cases are predicted will be increased into 3 million cases per year or grow 40% from 2020 data. It is also estimated the number of deaths due to breast cancer will be one million death per year in 2040. In Indonesia, the number of new breast cancers reached 68,858 cases (16.6%) of a total of 396,914 new cases of cancer in 2020. ​ The incidence and mortality rates of breast cancer are 44 and 15.3 per 100,000 population, respectively in Indonesia. The most common breast cancer treatments used currently are surgery, chemotherapy, and radiation. These three treatments involve a rather invasive approach and often causes side effects. Serious side effects can reduce a patient's quality of life, lead to non-compliance to chemotherapy, and lead to drug resistance.​ Some cancer patients use alternative therapy such as complementary medicine including herbal medicine to treat the cancer. Patients try to discover and utilize natural-derived anti-cancer drugs because it believes has fewer side effects and more affordable. One of Indonesia plant which is therapeutically beneficial is Ficus deltoidea. Ficus deltoidea leaves had been used in traditional medicine to treat diabetes, inflammation, diarrhoea, cancer and infections. F. deltoidea leaves contained flavonoids, saponins, tannins, steroids and terpenes which known for its anticancer effect.